THE INFLUENCE OF TEAMWORK AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT BANDAR LAMPUNG UNIVERSITY - Cecilia Priscilla Natalie; Iskandar Ali Alam (ZILLZELL MEDIA PRIMA, 2024)
The role of employees is very important to determine the success of the institution. It is regularly necessary to evaluate the performance of each employee to ensure that they have completed the job with enough responsibility and commensurate with what is expected by the institution. This study intends to see the effect of teamwork and work discipline on employee performance at Bandar Lampung University. This research is quantitative research. Data collection techniques use questionnaire or questionnaire methods. The sample in this study was 32 employees of Bandar Lampung University. The data analysis method uses the help of IBM SPSS Version 25 software. The results of this study explain that: 1). Teamwork does not have a significant effect on employee performance at Bandar Lampung University. 2). Work discipline in this study has a positive and significant effect on employee performance at Bandar Lampung University.